PENEGAKAN HUKUM PIDANA TERHADAP TINDAK PIDANAPENCUCIAN UANG (TPPU) YANG BERASAL DARI HASIL PENYUAPAN (ANALISIS PUTUSAN NOMOR : 38/PID.SUS/TPK/2013/PN.JKT.PST) - Mirza Erwinsyah; Bismar Nasution; Mahmud Mulyadi; Edi Yunara (Universitas Sumatera Utara, 2018)
ABSTRACT Background Bribery Bribes posing a threat to economic stability may undermine democratic institutions and values, ethical values, fairness, discriminatory nature, undermine ethics and honest business competition, injure sustainable development and enforceability of the law. The problems in this thesis are how the Corruption Crime formulation according to the Corruption Act, How is the Money Laundering Formulation under Law No.8 Year 2010 and How is the analysis of criminal law against Money Laundering Crime from Criminal Acts of Bribery On Decision Number: 38/ PID.SUS/TPK/2013/PN.JKT.PST.The conclusion in this thesis is a special legislation regulating the criminal act of corruption already exists. In Indonesia alone, the law on corruption has been 4 (four) times changed. The Crime of Money Laundering as stipulated in Law no. 8 Year 2010 on Prevention and Eradication of Money Laundering Crime can be classified into 2 (two) types, namely: Crime of Money Laundering and Passive Money Laundering Crime. Based on the indictment, the case is registered with number 38 / PID.SUS / TPK / 2013 / PN.JKT.PST. The defendant was charged with a layered article using 2 (two) Laws namely the Eradication of Corruption and the Criminal Act of Money Laundering. Keywords : Law Enforcement, Criminal, Money Laundering Crime, Bribery.